Effect of soilless media on nutrient uptake and yield of tomato (Solanum lycopersicum) - Spehia, Ranjit Singh; Singh, Shailesh Kumar; Devi, Meera; Chauhan, Nirmla; Singh, Sukhpreet; Sharma, Deepak; Sharma, Jagjeet Chand (The Indian Journal of Agricultural Sciences, 2020)
Soilless culture provides an alternative to soil culture when serious soil problems (i.e. soil borne pests, soil salinity, chemical residues in soil, lack of fertile soil) create difficulties in traditional soil-based production. Soilless culture includes growing media, like cocopeat, vermiculite, perlite etc. or hydroponics system. The study was conducted during 2016 and 2017 to standardize growing media for soilless tomato (Solanum lycopersicum L.) production at Department of Soil Science and Water Management, Dr Y S Parmar University of Horticulture and Forestry, Solan, Himachal Pradesh, India. The treatments consisted of different growing media, viz. cocopeat alone (control), cocopeat + vermicompost (70:30) and vermiculite + vermicompost (70:30). Plants were irrigated and fertigated with equal amount of Hoagland nutrient solution for meeting nutrient requirement. Treatment containing cocopeat + vermicompost (70:30) increased the nutrient uptake of N , P and K which was evident by the increased yield vis-à-vis control, i.e. cocopeat, alone. The results indicate that growing media consisting of cocopeat + vermicompost (70:30) enhances the quality and yield of tomato over the generally preferred growing media i.e. cocopeat, alone. The findings of the study will be helpful for the growers for enhancing the quality and yield of tomato under protected conditions to escape the problems faced in soil-based production system.